Autophagy in plant pathogenic fungi. (September 2016) - Liu, Xiao-Hong; Xu, Fei; Snyder, John Hugh; Shi, Huan-Bin; Lu, Jian-Ping; Lin, Fu-Cheng
Abstract: Autophagy is a conserved cellular process that degrades cytoplasmic constituents in vacuoles. Plant pathogenic fungi develop special infection structures and/or secrete a range of enzymes to invade their plant hosts. It has been demonstrated that monitoring autophagy processes can be extremely useful in visualizing the sequence of events leading to pathogenicity of plant pathogenic fungi. In this review, we introduce the molecular mechanisms involved in autophagy. In addition, we explore the relationship between autophagy and pathogenicity in plant pathogenic fungi. Finally, we discuss the various experimental strategies available for use in the study of autophagy in plant pathogenic fungi.